SOCIOCULTURAL AND ECONOMIC FACTORS INVOLVED IN THE HABIT OF SMOKING: AN EPIDEMIOLOGIC INQUIRY. (Fiep Bulletin - online, 2014)
Parents, stars, friends, and mass media advertising play a major role in leading subjects to start smoking. Publicity usually combines the social demands of different groups and leads those from poorer groups to believe that, by smoking, they will see their dreams and social expectations to come true, thus increasing smoking among more easily influenced people. Aim to define common characteristics of smokers and how they consider their smoking habit. The present epidemiological crosssectional descriptive study evaluated 152 male and female subjects who filled out a previously validated form and answered the adapted Fagerström Tolerance Questionnaire; both included objective questions. Study results are presented as percentages and absolute numbers in simple frequency graphs and tables. The study was carried out in accordance with ethical and legal requirements. Age of onset: 11-15 years of age in 78.3% of study subjects; smoking duration: > 10 years in 26.97%; anxiety was present in 73.03%; 51.97% smoked because of anxiety; 38.81% did not feel well without smoking; 69.74% were aware of smoking risks but did not want to quit; and 62.50% reported that social and television influences led them to smoke. According to study results, smoking is subject to social, familiar, and psychological influences.
Keywords: Smoking; Smoking habit; Anxiety